The Napping house - Wood, Audrey; Wood, Don, 1945- (San Diego : Harcourt, 1996)
In this cumulative tale, a wakeful flea atop a number of sleeping creatures causes a commotion, with just one bite.
"Red Wagon Books."
Cover title.
On board pages.
3.8
K-3
Keywords: Fleas -- Fiction; Sleep -- Fiction; Board books for children, English; Fleas -- Fiction; Sleep -- Fiction